ANALISIS PELAKSANAAN KEWENANGAN LEMBAGA OMBUDSMAN DAERAH (LOD) DALAM MENANGANI LAPORAN/KELUHAN MASYARAKAT DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - USISA ROHMAH, USISA ROHMAH (Politika: Jurnal Ilmu Politik, 2013)
Abstract Based on the 2008 DIY Gubernatorial of Number 21 LOD has the authority to supervise to the issue of mismanagement in the public service in Daerah Istimewa Yogyakarta (DIY), LOD is not designed to be an extra judiciary. Institution of the ombudsman as an institution of government control in handling and becamea symbol of the area who want to create good governance, efforts to prevent corruption, protecting the public, and implement democracy by providing good service to the community. Key words: Ombudsman, Authority, Democratic institutions